Development of an E-Module Adapted to the Independent Curriculum Informatics Subject on the Basic Elements of Technology and Information for Phase E Grade 10 Students - Afri Ola Dewi; Hendri; Yasdinul Huda; Rizky Ema Wulansari (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop an e-module for Informatics learning based on the Independent Curriculum, focusing on the Basic Elements of Technology and Information for grade X phase E students. The development employed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) to produce a systematic structure and contextual content. Validation results indicated that the e-module was in the valid category, while practicality tests from teachers and students showed it to be very practical and practical, respectively. Effectiveness testing also demonstrated improved learning outcomes in the experimental class compared to the control class. These findings highlight that the e-module effectively facilitates the understanding of abstract Informatics concepts, encourages higher-order thinking skills, and increases learning motivation. Therefore, the developed e-module is considered valid, practical, and effective for use, with potential adaptability to support learning in other subjects.